Influence of hypobaric hypoxic conditions on ocular structure and biological function at high attitudes: a narrative review - Wang, Yuchen; Yu, Xinli; Liu, Ziyuan; Lv, Zhongsheng; Xia, Huaqin; Wang, Yiren; Li, Jiaxi; Li, Xuemin (Frontiers in Neuroscience, 2023)
Abstract: (1) Background: With the development of science and technology, high-altitude environments, involving aviation, aerospace, and mountainous regions, have become the main areas for human exploration, while, such complex environments can lead to rapid decreases in air and oxygen pressure. Although modern aircrafts have pressurized cabins and support equipment that allow passengers and crew to breathe normally, flight crew still face repeated exposure to hypobaric and hypoxic conditions. The eye is a sensory organ of the visual system that responds to light and oxygen plays a key role in the maintenance of normal visual function. Acute hypoxia changes ocular structure and function, such as the blood flow rate, and can cause retinal ischemia. (2) Methods: We reviewed researches, and summarized them briefly in a review; (3) Results: The acute hypoxia affects corneal, anterior chamber angle and depth, pupils, crystal lens, vitreous body and retina in structure, moreover, the acute hypoxia does obvious effect on visual function, for example, vision, intraocular pressure, oculo-metric features and dynamic visual performance, visual field, contrast sensitivity and color perception. (4) Conclusion: We summarized the changes in the physiological structure and function of the eye in hypoxic conditions and to provide a biological basis for the response of the human eye at high-altitude.